Probabilistic modeling and risk characterization of the chronic aflatoxin M1 exposure of Hungarian consumers - Farkas, Zsuzsa; Kerekes, Kata; Ambrus, Árpád; Süth, Miklós; Peles, Ferenc; Pusztahelyi, Tünde; Pócsi, István; Nagy, Attila; Sipos, Péter; Miklós, Gabriella; Lőrincz, Anna; Csorba, Szilveszter; et al. (Frontiers in Microbiology, 2022)
Aflatoxin contamination can appear in various points of the food chain. If animals are fed with contaminated feed, AFB1 is transformed – among others – to aflatoxin M1 (AFM1) metabolite. AFM1 is less toxic than AFB1, but it is still genotoxic and carcinogenic and it is present in raw and processed milk and all kinds of milk products. In this article, the chronic exposure estimation and risk characterization of Hungarian consumers is presented, based on the AFM1 contamination of milk and dairy products, calculated with a probabilistic method, the two-dimensional Monte-Carlo model. The calculations were performed using the R plugin (mc2d package) integrated into the KNIME (Konstanz Information Miner) software. The simulations were performed using data from the 2018-2020 food consumption survey. The AFM1 analytical data were derived from the Hungarian monitoring survey and 1,985 milk samples were analyzed within the framework of the joint project of the University of Debrecen and the National Food Chain Safety Office of Hungary (NÉBIH). Limited AFM1 concentrations were available for processed dairy products, therefore a database of AFM1 processing factors for sour milk products and various cheeses was produced based on the latest literature data, and consumer exposure was calculated with the milk equivalent of the consumed quantities of these products. For risk characterization, the calculation of hazard index (HI), Margin of Exposure (MoE) and the hepatocellular carcinoma incidence (HCCi) were used. The results indicate that the group of toddlers that consume a large amount of milk and milk products are exposed to a certain level of health risk. The mean estimated daily intake (EDI) of toddlers is in the range of 0.008-0.221 ng kg-1 bw day-1, the 97.5th percentile exposure of toddlers is between 0.013 ng kg-1 bw day-1 and 0.379 ng kg-1 bw day-1, resulting in a hazard index above 1. According to our study, the exposure of older age groups does not pose an emergent health risk. Nevertheless, the presence of carcinogenic compounds should be kept to a minimum in the whole population.